Asymptomatic Infection in Decompensated Full-Thickness Corneal Grafts Referred for Repeat Penetrating Keratoplasty. Issue 4 (April 2017) - Nahum, Yoav; Leon, Pia; Ricci-Filipovic, Benedetta Azzurra; Camposampiero, Davide; Ponzin, Diego; Busin, Massimo
Abstract : Purpose: We report a case series of asymptomatic infections affecting failed corneal grafts in patients referred for repeat penetrating keratoplasty (PK). Methods: In this retrospective, noncomparative, interventional case series, we reviewed the medical records of all repeat PK procedures performed at Villa Serena-Villa Igea private Hospitals (Forlì, Italy) between January 2011 and March 2016. Specifically, preoperative and postoperative slit-lamp examinations, and the results of histological and bacteriological examinations, were noted. Results: Fifty-three repeat PKs were performed in the study period. All patients were referred because of long-standing graft decompensation with stromal scars or surface irregularities, thus unsuitable for endothelial keratoplasty. None was referred because of presumed infection. Histological examination of the explanted buttons showed the presence of microorganisms of various types in 7 eyes. Cultures were positive in 4 of these cases and in one additional case Staphylococcus aureus was grown in culture, but was not seen in the histology specimen. None of the patients presented with unusual pain, tearing, or discomfort. Preoperative abnormal clinical findings included epithelial defect (n = 6), focal whitening of corneal stroma (n = 5), crystalline keratopathy (n = 1), and an elevated pigmented lesion (n = 1). After repeat PK, recurrence of the infection was seen in 5 of 7 (71%) cases, 2 of which required a third PK procedure. Conclusions: Apparently quiet eyes with failed PK can harbor slow-growing asymptomatic infection. An epithelial defect in a failed PK graft should raise suspicion of infection. Routine cultures and histological examination of the excised corneal buttons are instrumental in the diagnosis of these infections and can guide further treatment.